Validation and Measurement of Psychometric Properties of the “Nursing Work Environment Questionnaire” (NWE-q) in Italian Nurses - Vitale E; Chang YC (Risk Management and Healthcare Policy, 2024)
Elsa Vitale,1 Yun-Chen Chang2,3 1Department of Mental Health, Local Health Authority of Bari, Bari, Italy; 2School of Nursing and Graduate Institute of Nursing, China Medical University, Taichung, Taiwan; 3Nursing Department, China Medical University Hospital, Taichung, TaiwanCorrespondence: Yun-Chen Chang, School of Nursing and Graduate Institute of Nursing, China Medical University, Beitun District, Taichung City, 406, Taiwan, Tel +886 983503901, Email lisacow@mail.cmu.edu.twBackground: Evidence suggests that an optimal workplace is a physical, chemical, biological, organizational, social, and cultural condition in which each element contributes to the employer’s condition.Purpose: To develop a nursing work environment questionnaire (NWE-Q).Patients and Methods: Convergent validity was measured using Pearson’s correlation test. Internal consistency for each dimension of the Nursing Work Environment questionnaire (NWE-q) was performed thanks to the Cronbach’s alpha coefficient. Construct validity and factor structure of the data were also assessed. Reliability was evaluated by measuring internal consistency. Interclass correlation coefficient and convergent validity were also assessed. Group validity was evaluated according to the sociodemographic characteristics collected using an independent t-test.Results: 376 nurses participated in this study. Both Kaiser–Meyer–Olkin measures of sampling adequacy were, and the Bartlett test of sphericity showed very strong evidence. Owing to oblique rotation, three main sub-dimensions were defined with good internal consistency for all items of the NWE-q (27 items), and each sub-dimension was registered. Very strong interclass correlations were assessed for the NWE-q total scores and for each sub-dimension, with the exception of the system dimensions, in which the interclass correlation showed a weak relationship. Strong positive evidence was found between the NWE-q for both the total and each sub-dimension correlated with the items of both the individual and organizational validated nursing performance questionnaires. Strong evidence was observed for both the organizational and system subdimensions according to shift and gender.Conclusion: The NWE-q was promptly completed in the online mode, and its scoring characteristics seemed to be more accessible and simpler to adopt.Keywords: environment, nurse, psychometric properties, reliability, validity